Preliminary Results of a Cardiac Rehabilitation Program in Patients with Compensated Heart Diseases in Sub-Saharan Africa (Benin): A Pilot Study - KPADONOU GODONOU, TOUSSAINT; FIOGBE, E.; DATIE, AM; ALAGNIDE, HOUNTONDJI ETIENNE; NIAMA NATTA, DIDIER; HOUNGBEDJI, M. GERMAIN; AZANMASSO, H; MASSOUGBODJI, M (My University, 2013)
Background: In sub-Saharan Africa, socio-economic conditions limited access to cardiac rehabilitation programs (CRP) designed according to the usual models in the treatment of patients with cardiovascular disease (CVD). Objective: To evaluate the effectiveness of a program of CRP based on Borg scale of perceived effort. Methods: A Prospective, descriptive study aimed to be analytical focused on 27 patients with compensated heart diseases (CHD) included in a CRP for 30 workouts during 10 weeks. These patients were evaluated by Borg scale of perceived exertion with measuring heart rate (HR), body mass index (BMI) and blood pressure (BP) of rest at the beginning and at the end of the program. Results: It was recorded a significant reduction in the heart rate (p<0.0001), systolic BP (p<0.0001) and diastolic BP (p=0.0002) while BMI reduction did not get a significant reduction (p=0.15). Discussion: According to the studies encountered, intensities of physical activities such as those which have been subjected to patients are sufficient to cause different physiological adaptations noted at the end of this present program. Conclusion: This CRP appears to be an alternative to physical training in patients with CHD from socially disadvantaged conditions.
Keywords: Rehabilitation program effort; Compensated heart; disease; Borg scale; Sub-saharan Africa